Beyond world class building character, relationships, and profits - Ross, Alan M. (Dearborn Trade Pub., 2002)
In Beyond World Class, leaders learn the process of "auditing" for people values, including how to: *Envision the future to create solutions for problems that are not yet visible. *Redirect staff accountability to encourage the company to reach its fullest potential on behalf of the customer. *Implement six human-values principles that will transform any organization. Practical how-to combined with best practices case studies illuminate for CEOs, executives, and senior managers the strategies that drive organizational excellence. Beyond World Class proves the benefits of incorporating employees, customers, and suppliers into a culture of character.